2017
DOI: 10.1177/0957650917720560
|View full text |Cite
|
Sign up to set email alerts
|

Experiment study of the winglet-cavity tip on the aerodynamic performance in a turbine cascade

Abstract: The effects of a novel winglet-cavity tip on the flow field and aerodynamic performance of a turbine blade with tip clearance have been investigated in a low-speed wind tunnel. A calibrated five-hole probe is used for the measurement of three-dimensional flows downstream of the cascade. The method of oil-flow visualization is used to show the endwall flow field structure. The distribution of endwall static pressure is measured particularly by using the special moveable endwall. The downstream results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Different methods have already been carried out to improve the tip leakage flow, such as passive flow controls and active flow controls. Some popular passive flow control methods of tip clearance flow which consist of winglet tips, 4,5 cavity tips 6,7 and wingletcavity tips 8,9 have been studied to improve the tip leakage flow. Moreover, the active control methods of boundary-layer flow separations have been applied normally for the delay or complete elimination of flow separations, and make the decelerated near-wall fluid excited by exerting either an additional momentum or a vorticity to the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have already been carried out to improve the tip leakage flow, such as passive flow controls and active flow controls. Some popular passive flow control methods of tip clearance flow which consist of winglet tips, 4,5 cavity tips 6,7 and wingletcavity tips 8,9 have been studied to improve the tip leakage flow. Moreover, the active control methods of boundary-layer flow separations have been applied normally for the delay or complete elimination of flow separations, and make the decelerated near-wall fluid excited by exerting either an additional momentum or a vorticity to the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…For conventional turbomachinery, the reduction of aerodynamic losses can be achieved by changing its geometry, such as the tip leakage loss can be controlled by the tip shape. [17][18][19][20][21][22][23] Evidence has been shown that the intensity and position of shocks are both sensitive to the blade profile of conventional turbomachinery. The strake of the ram-rotor is similar to the blade.…”
Section: Introductionmentioning
confidence: 99%